Edible Insects: Islamic Perspectives on Entomophagy and Future Foods: Islamic Perspectives on Edible Insects - Riyaz, Muzafar (SHAHIH: Journal of Islamicate Multidisciplinary, 2023)
Edible insects have gained increasing attention as a sustainable and nutritious alternative protein source. Islam, being one of the world's major religions, plays a significant role in shaping dietary practices and food choices for its adherents. This study explores into the intersection of entomophagy, Islamic beliefs, and the potential of edible insects as future foods, examines Islamic perspectives on food, and highlights the potential compatibility of entomophagy with Islamic dietary laws (Halal). It also explores relevant Islamic principles and teachings that may influence the acceptance and adoption of edible insects as a viable food source within the Muslim community. Moreover, the study investigates the environmental and sustainability aspects of edible insects, aligning them with Islamic principles of stewardship and responsible resource utilization. It discusses the nutritional benefits of edible insects, considering their potential to address global food security challenges and malnutrition issues prevalent in many Muslim-majority countries.